Outcomes of Community Pharmacy Interventions on Patients with Medicines Under Additional Monitoring - Aizpurua-Arruti X; Benrimoj SCI; Goyenechea E; Isla A; Oñatibia-Astibia A; Malet-Larrea A; Gastelurrutia MÁ; Cuevas O; Rodríguez-Castejón J; Domingo-Echaburu S; Solinís MÁ; García M; et al. (Dove Medical Press, 2024)
Xabier Aizpurua-Arruti,1,2 Shalom Charlie I Benrimoj,3 Estibaliz Goyenechea,1 Arantxa Isla,2,4 Ainhoa Oñatibia-Astibia,1 Amaia Malet-Larrea,1 Miguel Ángel Gastelurrutia,1,3 Olatz Cuevas,1 Julen Rodríguez-Castejón,2,4 Saioa Domingo-Echaburu,5 María Ángeles Solinís,2,4 Montserrat García,6 Ana del Pozo-Rodríguez2,4 1Official Pharmacist Association of Gipuzkoa, Donostia / San Sebastián, Spain; 2Pharmacy Practice Research Group, PharmaNanoGene Group, Faculty of Pharmacy, University of the Basque Country UPV/EHU, Vitoria-Gasteiz, Spain; 3Pharmaceutical Care Research Group, Faculty of Pharmacy, University of Granada, Granada, Spain; 4Bioaraba, Microbiology, Infectious Disease, Antimicrobial Agents, and Gene Therapy, Vitoria-Gasteiz, Spain; 5Osakidetza Basque Health Service, Debagoiena Integrated Health Organisation, Pharmacy Service, Arrasate, Spain; 6Basque Country Pharmacovigilance Unit, Osakidetza Basque Health Service, Galdakao-Usansolo Hospital, Galdakao, SpainCorrespondence: Ana del Pozo-Rodríguez, Pharmacy Practice Research Group, PharmaNanoGene Group, Faculty of Pharmacy, University of the Basque Country UPV/EHU, Vitoria-Gasteiz, Spain, Email ana.delpozo@ehu.eusPurpose: Additional monitoring (AM) medicines include (i) medicines containing a new active substance; (ii) biological medicines; (iii) medicines with conditional approval or authorized in special situations; (iv) medicines which require further studies; (v) medicines that have specific requirements regarding the reporting of suspected adverse drug reactions (ADRs). When AM medicines are marketed, their most common ADRs are known, but safety information is limited because relatively rare ADRs are often not detected in clinical trials. Their AM status warrants real-world studies to identify other safety issues; however, such studies are lacking. Correct use and adherence to dosage regimen by patients are key factors for the evaluation of the safety and efficacy of medicines. The objective of this work was assessing the impact on safety, adherence, use and knowledge (U&K) about medicines and patient's quality of life (QOL), of community pharmacist (CP)-led interventions in a new service focused on AM medicines targeted at three prevalent chronic diseases: diabetes mellitus type 2, chronic obstructive pulmonary disease and cardiovascular disease.Patients and Methods: A prospective interventional cohort study was conducted with a 6-month follow-up in 27 community pharmacies (145 patients). Safety, adherence to treatment, patient U&K and QOL were assessed at follow-up visits (months 0, 3 and 6).Results: The number of detected ADRs was 163 with 41 patients referred to the doctor. At baseline, 24.1% of the patients were non-adherent, mainly due to unintentional causes. After six months and 130 interventions by CPs on adherence, a significant reduction to lower than 5.8% was achieved. The inadequate U&K of medicines also decreased, from 47.6% to 7.9% after 182 interventions. Also, the patient's QOL improved.Conclusion: A new patient-centered pharmacy service provides some evidence on the important role of CP in assisting the proper and safe use of AM medicines, improving patient health outcomes. Keywords: community pharmacy, medicines under additional monitoring, safety, adherence, use and knowledge, pharmaceutical care